Kindergartens and nurseries in central portugal. assessments of indoor environment quality - Pinto, Manuel (2021)
The Indoor Environment Quality study takes on a very significant challenge when analyzed, mainly, in buildings that encompass a more sensitive and susceptible type of population, as is the case of children. To comply with a set of requirements, namely the concentration of pollutants and the conditions of hygrothermal comfort, is a necessary condition to keep an interior environment suitable for the permanence of the occupants. A research project, that studied Indoor Environment Quality in four buildings which hold nurseries and kindergartens, was carried out in two cities in central Portugal, Viseu and Covilhã. The following main conclusions may be drawn: most compartments are not comfortable in terms of ambient temperature, but the relative humidity has reasonable values. Air change rates generally have low values and the measured pollutants have worrying values. Based on the observed problems and reached conclusions, some recommendations are proposed.